Self-Synchronisation of Vibrating Screen Unbalanced Mechanisms as Function of Location, Unbalanced Moment and Operating Frequency - Gregory, Ziggy (Curtin University, 2018)
Most of the vibrating feeder equipment operate with two vibrators where the synchronisation is obtained either by electronically controlling phases of driving electric motors or using kinematic couplings like gears, v-belts or toothed belts. The objective of the research was to confirm if two vibrators on the same testing rig will self–synchronise when operating in the same and opposite directions. Tests were also done for two vibrators running with different frequencies.